2017
DOI: 10.1152/ajpheart.00002.2017
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cAMP deactivates ischemia-reperfusion-induced microvascular hyperpermeability via Rap1-mediated mechanisms

Abstract: Approaches to reduce excessive edema due to the microvascular hyperpermeability that occurs during ischemia-reperfusion (I/R) are needed to prevent muscle compartment syndrome. We tested the hypothesis that cAMP-activated mechanisms actively restore barrier integrity in postischemic striated muscle. We found, using I/R in intact muscles and hypoxia-reoxygenation (H/R, an I/R mimic) in human microvascular endothelial cells (HMVECs), that hyperpermeability can be deactivated by increasing cAMP levels through app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Epac1 has been shown to reduce myocardial damage in response to I/R [ 20 ]. Additionally, work in muscle and endothelial cells showed that Epac1 reduced hyper-permeability following exposure to I/R [ 21 ]. We previously reported that Epac1 regulated ZO-1 and occludin in the mouse retina and in retinal endothelial cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epac1 has been shown to reduce myocardial damage in response to I/R [ 20 ]. Additionally, work in muscle and endothelial cells showed that Epac1 reduced hyper-permeability following exposure to I/R [ 21 ]. We previously reported that Epac1 regulated ZO-1 and occludin in the mouse retina and in retinal endothelial cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse IL-1β/IL-1F2 Quantikine ELISA Kit (catalog SMLB00C), human IL-1β/IL-1F2 Quantikine tection elicited acutely by raising endothelial cell concentration of cAMP (40). In these studies, cAMP restored endothelial permeability in response to multiple permeability-increasing stimuli such as thrombin (40) and ischemia/reperfusion (41). The barrier protection was ascribed to cAMP-dependent activation of guanine nucleotide exchange factor (EPAC), which promoted exchange of GTP in the small GTPase Rap1 (40,42).…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported administration of 007 to suppress vascular endothelial growth factor (VEGF)-induced vascular hyperpermeability in murine skin. 34) Similarly, 007-induced activation of the Epac/Rap1 pathway was shown to inhibit microvascular hyperpermeability caused by PAF in the rat mesentery, 68) disruption of the endothelial barrier caused by toxins derived from Pseudomonas aeruginosa, a major nosocomial infection agent, 69) ischemia-reperfusion-induced microvascular hyperpermeability in skeletal muscle, 70) and cytokine-induced retinal vascular permeability. 71) Furthermore, cAMP-elevating GPCR agonists such as prostaglandin I2 and its stable analogs like iloprost and beraprost, prostaglandin A2, and adrenomedullin are known to exert Rap1-dependent protective effects against pulmonary endothelial barrier dysfunction during acute pulmonary injury induced by LPS administration and mechanical ventilation.…”
Section: Rap1 As a Potential Drug Target For Vascular Hyperpermeabilitymentioning
confidence: 98%